Private Law Between Life and Death (Revista da Faculdade de Direito, Universidade de São Paulo, 2005)
This work discuses private law aspects of embryo’s warming and its utilization in medical research on embryonic stem-cells, cloning for therapeutic matters, abortion of anencephalic fetuses, and autonomy of will concerning euthanasia.